Evaluación de cinco protocolos de conservación de tejidos en chigüiro (Hydrochaeris Hydrochaeris) (Linnaeus, 1766) (2010)
Titulo en ingles:  Evaluation of five protocols of conservation‘s techniques in chiguiro Hydrochaeris hydrochaeris (Linnaeus, 1766) tissues.ABSTRACT:   Bodies conservation is a technique that uses the formalin chemical almost exclusively. It´s use dehydrates the tissues, takes the tissues dissection very hard and volatilized contaminants fumes. With the purpose to carry out morphological studies in chigüiros (Hydrochaeris hydrochaeris) and minimize contaminants effects for exclusive use of formalin, tests were made with five conservations protocol´s, using compounds such: Formalin at 5, 12, 14, 16 y 18 %; Phenol at 3, 5, 7 and 8 %; glycerin at 1, 5 and 10 %; Ethanol at 5, 7, 10 y 12 %, using two experimental animals for each one. Specimens were anesthetized with a mixture of atropine, midazolam, ketamine and xylazine. Exsanguinations and application of conservation protocols, was made through the carotid artery, using an injection fluids pump. Volume applied was calculated according with ten per cent of corporal weight of each specimen. Dissection was begun ten days after conserving protocols applied. Muscle tissues were took to different times (30, 60, 90, 120 after protocols applications), to verified the actions of each protocol. Protocol 1 is behaving properly, because the corpses were preserved in good condition during the study period, allowing the realization of dissections and supported the manipulation of parts, protecting them from the climatic conditions prevailing in the area. The protocol two and three had similar behavior to one, the tissues were softer, but more dehydrated by the use of higher concentrations of formaldehyde. It is noteworthy that vapor contamination was significantly reduced. In protocol 4, the tissues of the head, neck, upper extremities and thoracic viscera, were kept well hydrated and better. Protocol 5, follows the same pattern of others. The preservation of tissues was good, with no perceived excess volatility of gas, the dissection carried out more comfortably. Still need to analyze the histological studies relating to the last sampling (120 days) to determine the effect on the tissues. It is expected; the study is completed, and has protocols that ensure greater conservation, soft tissue and substantial decrease in gas pollution.Key words: Corpses, capybara, pollution, formaldehyde, gas.RESUMEN:   La conservación de cadáveres se ha realizado haciendo casi el uso exclusivo de formol. Esto deshidrata los tejidos, haciendo dificultosa la disección y provocando vapores contaminantes. Con el fin de adelantar estudios morfológicos en chigüiros (Hydrochaeris hydrochaeris) y de minimizar los efectos contaminantes por el uso exclusivo del formol, se hicieron ensayos con cinco protocolos de conservación, utilizando componentes como: Formol al  5, 12, 14, 16 y 18 %; Fenol al 3, 5, 7 y  8 %; Glicerina al 1, 5 y 10 %; Etanol al 5, 7, 10 y 12 %, usando dos ejemplares de chigüiro para cada uno de los procedimientos. Los animales experimentales fueron anestesiados con un coctel anestésico a base de Atropina, Midazolan, Ketamina y Xilazina. La exanguinación y aplicación de protocolos se hizo vía arteria carótida, con ayuda de una bomba  de fluidos automatizada. El volumen aplicado se cálculo con base al 10 % del peso corporal del individuo experimental. La disección se inició a los diez días de aplicado el protocolo, se tomaron muestras de tejido muscular a diferentes tiempos para evaluar el efecto conservante. El protocolo uno se comporto en forma adecuada, dado que los cadáveres se conservaron en buen estado durante el tiempo de estudio,  permitiendo la realización de  disecciones y   soportado la manipulación de las piezas, protegiéndolas de las condiciones climáticas imperantes en la zona. El protocolo dos y tres tuvieron un comportamiento similar al uno, los tejidos son más suaves, pero más deshidratados por el uso de concentraciones más altas de formol. Es de resaltar  que la contaminación por vapores, se redujo considerablemente.  Con el protocolo 4, los tejidos de cabeza, cuello, vísceras torácicas y miembros torácicos, se han conservado bien y mejor hidratados. El protocolo 5, siguió el mismo patrón de los demás. La conservación de los tejidos,  fue buena, sin  percibirse exceso de volatilidad de gases, realizándose la disección con mayor comodidad. Esta por analizar los estudios histológicos correspondientes a la última toma de muestras (120 días) para determinar el efecto en los tejidos. Se espera,  finalizado el estudio,  contar con protocolos que aseguren mayor conservación, suavidad de tejidos y disminución sustancial de contaminación por gases.Palabras Clave: Cadáveres, capibara, contaminación, formol, gases.